Factors influencing extracorporeal shockwave lithotripsy efficiency in the management of lower pole stones - Miheler, Dóra-Andrea; Reman, Tibor; Gherasim, Raul; Vida, Olivér A.; Porav-Hodade, Daniel; Mártha, Orsolya (Medicine and Pharmacy Reports, 2025)
Objectives. The low efficacy of extracorporeal shock wave lithotripsy (ESWL) in the treatment of lower pole stones is well known; the parameters which influence this effect are still under debate: patient age, stone size, presence of double J stent, body mass index (BMI), and radiological parameters of the lower calyx, such as infundibulopelvic angle (IPA), infundibulum length (IL), and width (IW) of patients and the skin-stone size. Methods. We studied the effectiveness of extracorporeal shock wave lithotripsy (ESWL) in the treatment of lower calyx stones. All patients were investigated by uro- CT or intravenous urography (IVU), or kidney, ureter, bladder (KUB) radiography to confirm the diagnosis. J stents were inserted before therapy in 64 (18.6%) renal units. Factors affecting success, stone-free rate and complications were analyzed. We measured the skin-stone distance (SSD) of the lower calyx on 39 uro-CT image data, and infundibulum length, width and infundibulopelvic angle on 31 intravenous urography (IVU). Results. Our retrospective study (between 2021 and 2024) included a total of 344 patients who underwent ESWL for lower calyceal stone (172 men, 172 women) with an average stone size 9.093±2.829 mm. 68.605% of patients became stone-free after the first ESWL session. The average skin stone distances measured in 0°, 45°, 90° angles were 96.5 ± 24.92 mm. Using the Chi-square test, we concluded that previously stented patients had a statistically lower stone-free rate (SFR) than those without a stent. (p=0.0078). The body mass index (BMI) of patients also influenced the SFR, as calculated with an Unpaired t-test and Welch correction (p = 0.002). We did not find any statistically significant differences between skin-stone sizes of patients with or without successful stone fragmentation (p=0.1147), and infundibulum length (p=0.07), infundibulum width (p=0.7681), and infundibulopelvic angle (p=0.996). Conclusions. Single ESWL sessions often fail to achieve stone fragmentation and elimination, as this study shows. The success of ESWL sessions can be affected by the anatomical position of the stone, a lower pole kidney stone, the presence of pre-procedural double J stenting, and obesity.